Incidencia y severidad de Coptoborus ochromactonus en plantaciones de balsa Ochroma pyramidale (Cax. Ex Lam) y alternativas biológicas para su manejo. - Zambrano Monserrate, Andrés Jasir (2017)
The Ochroma pyramidale (Cax. Ex Lam) is a forest and timber species that has great demand in the international market. It is cultivated in a natural way and for reforestation, especially in the subtropical forest of Ecuador, where it is one of the most exploited forest and timber resources; For this reason is one of the economic items of importance in the economy of our country. The Escolítids, together with their symbiotic fungi, cause in the host trees a disease called regressive death. Coptoborus ochromactonus is an Ochroma pyramidale associated with Ochroma pyramidale (Cax. Ex Lam) in Ecuador whose specific name derives from the same tree which has caused damages of up to 50% in plantations of 3 years of age. The adult Coptoborus ochromactonus, is a transmitter of the fungus Fusarium spp, which lives in symbiosis, which damages the plant leaving it withered and causing the tree to die. This research was carried out in order to determine the incidence and health of C. ochromactonus in the Ochroma pyramidale raft (Cax. Ex Lam), and to search for biological alternatives in plantations of 1, 2, 3 years of age For its control. In the plantations of 3 years a very high percentage of 88.92% and in the other two ages were very low, whereas the severity was also recorded in plantations of 3 years of age with a number of perforations of 860.0 perforations per Every 2 m that was evaluated. On the other hand, it was determined to find biological alternatives for its control of schools where an entomopathogenic organism B. bassiana native to C. ochromactonus was found which gave a lot of positive results in the laboratory inoculated to this insect pest. Key words: Coptoborus ochromactonus, ambrosia fungi, Fusarium, entomopathogenic fungi, Ochroma pyramidale.